2004
DOI: 10.1021/cg0497647
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Polymorphism of (2E)-2-Cyano-3-[4-(Diethylamino)phenyl]prop-2-enethioamide:  X-ray Structural Study and Polymorph Prediction

Abstract: Synthesis and crystallization of a polar organic compound (2E)-2-cyano-3-[4-(diethylamino)phenyl]prop-2-enethioamide (CDPE) gave two new crystalline polymorphs (1 and 2) and an acetonitrile solvate (pseudopolymorph, 3) of this compound. The third crystalline polymorph of CDPE (4) was described in the literature earlier. It was found that in crystalline polymorphs 1, 2, and 4 molecules adopt three different conformations. Experimental observations show that polymorph 1 is a predominant form of the CDPE compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The C≡N bond length (1.145 (2) Å), C?C (1.405 (2) Å) and C?O (1.2202 (18) Å) are in agreement with those observed before (Timofeeva et al, 2004;Azim et al, 1997). The S-H hydrogen bond length corresponds well to the the value 1.197 (9) Å from 247 observations yielded by the Cambridge Crystallographic Database (Allen, 2002).…”
Section: S1 Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…The C≡N bond length (1.145 (2) Å), C?C (1.405 (2) Å) and C?O (1.2202 (18) Å) are in agreement with those observed before (Timofeeva et al, 2004;Azim et al, 1997). The S-H hydrogen bond length corresponds well to the the value 1.197 (9) Å from 247 observations yielded by the Cambridge Crystallographic Database (Allen, 2002).…”
Section: S1 Commentsupporting
confidence: 82%
“…For related literature, see: Allen (2002); Azim et al (1997); Gao et al (2006); Timofeeva et al (2004); Xue et al (2004); Etter et al (1990).…”
Section: Related Literaturementioning
confidence: 99%
“…These results suggest that, under different crystallization conditions, it could be possible to crystallize another isomer of (I), as has been achieved, for instance, for the NLO material (2E)-2-cyano-3-[4-(diethylamino)phenyl]prop-2-enethioamide (Timofeeva et al, 2004).…”
Section: Commentmentioning
confidence: 77%
“…Timofeeva et al 22 and Nowell and Price 27 have found that RB simulations are superior to CA simulations. In this study, two factors have been postulated as being important: (1) E conformational error occurs during CA simulations because initial IM partial charges are used inappropriately with all new CA produced conformations, and (2) E unit cell optimization process during CA simulations is prone to the possibility of having E cohesive overwhelmed by E conformational .…”
Section: Discussionmentioning
confidence: 99%
“…The deviations using CA can be seen to be much larger than for RB strategy. Timofeeva et al 22 have suggested that the superiority of the RB over the CA strategy could be due to the inability of molecular mechanics to properly assess the conformational energy dependence with respect to torsion angles. There may be an alternative explanation for the poor performance of the CA strategy.…”
Section: Relative Importance Of Conformational and Cohesive Deviationmentioning
confidence: 99%